PENGELOLAAN PASCA PELEPASLIARAN DAN AKTIVITAS ORANGUTAN (Pongo pygmaeus wurmbii Groves, 2001) EX-CAPTIVE DI SUAKA MARGASATWA LAMANDAU - Ventie Angelia Nawangsari; Abdul Haris Mustari; Burhanuddin Masyud (Media Konservasi, 2016)
Orangutan is an endemic wild animal of Sumatra and Kalimantan (Borneo) Island. The population of Borneo orangutan decrease and become endangered caused by high damage of its habitat and illegal hunting. The conservation efforts needs to be done to maintain the population. One of this effort is release of ex-captive orangutan. One of the factors of the success of release is orangutan activity and post release management. The objective of this research was to analyze post-release management and daily activity of orangutan. Data collection of management was obtained through direct observation and interview to manager of release and veterinary. While data collection of orangutan activity through observation using focal-animal sampling method. The orangutan post-release management conducted by orangutan monitoring, supply additional feed in feeding site area, monitoring of reintoduction habitat, and medical examination of orangutan. The daily activity of ex-captive orangutan showed that rest activity had significantly different in adult and adolescent’s age class. The adults has duration of rest activity longer than the adolescents.Keywords: activity, orangutan, post-release